Optimal lymph node yield for long-term survival in elderly patients with right-sided colon cancer: a large population-based cohort study - Tianyi Liu; Shuai Jiao; Shan Gao; Yan Shi (BMC Cancer)
Abstract Background Although the recommended minimal lymph node yield (LNY) in colon cancer is 12, this standard remains controversial in elderly patients with right-sided colon cancer (RSCC) due to insufficient evidence. This study aims to clarify this issue by assessing the relationship between LNY and long-term survival in elderly patients with RSCC. Methods Data from the SEER database (split into 7:3 training and testing sets) and patients from the colorectal surgery departments of two tertiary hospitals in China (validation set) were analyzed. Elderly patients with stages I-III RSCC undergoing resection were included. The correlation between LNY and overall survival (OS) was evaluated by a multivariate model and the application of the restricted cubic spline curve (RCS). The odds ratios (ORs) for stage migration and the hazard ratios (HRs) for OS with increased LNY were estimated using Locally Weighted Scatterplot Smoothing (LOWESS), with structural breakpoints identified using the Chow test. Results The distribution of LNY was similar across the training (median: 18, IQR [14, 23]), testing (median: 18, IQR [14, 23]), and validation (median: 17, IQR [14, 20]) sets. Increasing LNY was associated with significantly improved OS in all datasets (Training set: HR = 0.983; Testing set: HR = 0.981; Validation set: HR = 0.944, all P < 0.001) after adjusting for confounders. Cut-point analysis identified an optimal LNY threshold of 18, validated across datasets, effectively discriminating survival probabilities. Conclusions A higher LNY is associated with improved survival. Our findings robustly support 18 LNYs as the optimal threshold for assessing the quality of lymph node dissection and prognosis stratification in elderly patients with RSCC.